Finding John Galt : people, politics, and practice in gifted education - Romey, Elizabeth A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
This volume covers significant highlights in the history of gifted education, addressing significant contributors to the field, important political and policy concerns, and programs and practices of note. The book's scope is holistic, using Ayn Rand's concept of "men [and women] of the mind" to frame giftedness as a quality of individuals that extends beyond the academic or "schoolhouse" setting and into a range of aspects of the lived human experience of gifted individuals.
Keywords: Gifted children -- Education -- United States -- History.; Gifted children -- Education -- United States -- Philosophy.; Teachers of gifted children -- Biography.; elektronické knihy; Biographies.; Education -- History.; Educational psychology.; History of education.; electronic books